Estudos de pré-formulação em formas farmacêuticas sólidas de uso oral para os fármacos desloratadina e etinilestradiol - Bissa, Isabela Pianna Veronez (2013)
Pre-formulation is an important stage in the research and development of new pharmaceutical formulations. The application of thermoanalytical techniques has been extended, in particular the differential scanning calorimetry (DSC), which is described as fast and suitable for quality control and development of new drugs. The aim of this study was to apply the thermal analysis and complementary techniques in pre-formulation studies as characterization of drugs, the compatibility study of drugexcipient and development and evaluation of solid dispersions. Desloratadine (DL), an antihistamine which has been widely used to treat allergic symptoms and stand out from other drugs in this therapeutic class by not showing sedative effects was fully characterized using six different techniques. Compatibility studies drug-excipient was also conducted. The excipients studied were dibasic calcium phosphate anhydrous, microcrystalline cellulose, corn starch, talc pharmaceutical, mannitol, magnesium stearate, polyvinylpyrrolidone K25 (PVP), stearic acid and anhydrous lactose. The DSC results suggested that the excipients microcrystalline cellulose, magnesium stearate, stearic acid and anhydrous lactose have possible interactions with the active ingredient through the disappearance or the change in enthalpy of fusion of the drug. In liquid chromatography analysis these results were confirmed by the appearance of peaks corresponding to the degradation products in the samples containing mixtures of these excipients. Ethinyl estradiol (EE) is an estrogenic component in oral contraceptives. It is present small dosages, difficult of low solubility and content uniformity. In this study, several processes to development of a solid dispersion with pharmaceutical excipients were evaluated using the technique of PXRD and DSC. The results showed that the process involving the use of solvents generally combined with excipients such as PVP have been effective in ensuring the dispersion of solid active ingredient EE, an important factor to increase the solubility and homogeneity of the drug in solid dosage formulations.